2010
DOI: 10.1007/s12291-010-0092-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D Supplementation in Hypertension

Abstract: Role of Vitamin D supplementation was studied in patients with hypertension. One hundred hypertensive patients (group I) were given conventional antihypertensive drugs while another 100 patients (group II), in addition, were supplemented with Vitamin D 3 (33,000 IU, after every 2 weeks, for 3 months). Besides diastolic and systolic blood pressure, serum calcium, phosphorous, alkaline phosphatase, albumin, albumin-corrected calcium, and 24 h urinary creatinine levels were estimated in both the groups before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
3
20
1
4
Order By: Relevance
“…They revealed that supplemental vitamin D3 and calcium have no effect on blood pressure (13). As well as, a clinical trial, showed supplemental vitamin D3 with antihypertensive regimen have stronger therapeutic effect than antihypertensive drug alone (14). Despite all the facts, we observed no association between supplemental calcium and vitamin D3 and blood pressure.…”
Section: Discussioncontrasting
confidence: 48%
“…They revealed that supplemental vitamin D3 and calcium have no effect on blood pressure (13). As well as, a clinical trial, showed supplemental vitamin D3 with antihypertensive regimen have stronger therapeutic effect than antihypertensive drug alone (14). Despite all the facts, we observed no association between supplemental calcium and vitamin D3 and blood pressure.…”
Section: Discussioncontrasting
confidence: 48%
“…Supplementation of vitamin D resulted in reduction of 0.2 mmHg of systolic BP for each increase of 1 ng/mL of vitamin D over three months (p = 0.02) [26]. Similarly supplementation of vitamin D (33,000 IU of vitamin D 3 , after every 2 weeks, for 3 months) in 100 hypertensive patients demonstrated significant decrease in systolic blood pressure [27]. In a meta analysis by Wu et al [28], oral supplementation of vitamin D was reported associated with significant reduction in systolic but not diastolic blood pressure [28].…”
Section: Intervention Studiesmentioning
confidence: 90%
“…Although the evidence from animal studies clearly links vitamin D to blood pressure, vitamin D supplementation studies on hypertension in humans yielded mixed results. Vitamin D 3 (33000 IU) administration for every 2-weeks for six months reduced systolic blood pressure significantly [63]. A large meta-analysis of 81 studies by Mirhosseini et al [64] reported that vitamin D improved blood pressure, dyslipidemia, and hypertension.…”
Section: Discussionmentioning
confidence: 99%